A preliminary study on factors that influence skin characteristics of UiTM'S staffs / Saiful Izwan Suliman, Tommy Julianto and Prof. Ir. Dr Shah Rizam Mohd Shah Baki - Suliman, Saiful Izwan; Julianto, Tommy; Mohd Shah Baki, Shah Rizam (Prof. Ir. Dr) (2009)
This study is a preliminary stage of further researches that identifies the factors that influence skin characteristics of UiTM's staffs based on experiments conducted in a lab. There is a serious concern among a population in Asia about possible adverse biological effects of environment exposure, lifestyle and food pattern. In this project, the effects of the factor on human skin are discussed, the skin topography was measured such as skin roughness, moisturize, elasticity, smoothness and transepidermal water loss were studied. Hundred staffs were selected to undergo a skin test and answer relevant questions. The skin tests were conducted by using Visionscan® VC 98 and the software SELS and Cutometer® MPA 580. From the skin tests, the characteristics of the skin of these subjects were determined and the factors that influence its conditions were recognized by analyzing the questionnaires. We found that from the several selected factors mentioned in the questionnaires, only two factors which are gender and supplement intake influence and affect the skin characteristics of the participants (UiTM's staffs). Meanwhile, other selected factors such as amount of water consumed, type of soap used, working environment and cosmetic product applied do not show significant effect or in other word do not affect and influence the skin characteristics of the subjects.